Kanban method in digital data processing - Csernoch, Mária; Szűcs, Edit Gizella; Máté, Domicián (International review of applied sciences and engineering (Online), 2025)
Current digital education operates as a push-system, despite the content and subject characteristics suggesting a need for a pull-system. One of the features of the push-system is a tool-centered approach, where the focus on tools, including both hardware and software, is the belief that it is possible to build knowledge inventory. The consequences of the push digital education approaches are that (1) the fundamental concepts of Computer Science are not being transferred, (2) the lack of the development of supporting methods, (3) and education does not seem to be interested in revealing the root causes and to be open for fundamental changes. This paper proposes the extension of the theory of the industrial pull systems to present as a potential solution to increase the effectiveness and efficiency of digital education and reduce or eliminate data processing inefficiencies generated by undereducated but misled end-users. In addition to theoretical discussions, it also delves into the detailed analysis, design, implementation, and testing of a real-world data processing problem. The presented problem, its analysis, solution, and accompanying discussion reveal how one of the tools (kanban) of lean production can be adapted to support the Just-in-Time philosophy in digital education, focusing on end-user programming.